2018
DOI: 10.1016/j.ypmed.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Using an integrated conceptual framework to investigate parents' HPV vaccine decision for their daughters and sons

Abstract: , Z. (2018). Using an integrated conceptual framework to investigate parents' HPV vaccine decision for their daughters and sons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 39 publications
5
54
1
Order By: Relevance
“…PAPM facilitates a better understanding of vaccine hesitancy by excluding parents who are not even aware that the HPV vaccine can be given to their child. Previous research has shown that in the absence (or incipient stages) of an HPV vaccination program for boys, the unaware group accounts for 28-58% of a randomly selected sample of parents 13,14 and have significantly lower HPV knowledge compared to unengaged, undecided and decided not hesitant parents. 14 To better understand the longitudinal decision of vaccine hesitant parents we dichotomized vaccine hesitant parents-in parents of boys and girls-as two distinct entities: "flexible" Note: OR = adjusted odds ratio for decided to/vaccinated versus unengaged/undecided/decided not (reference category).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PAPM facilitates a better understanding of vaccine hesitancy by excluding parents who are not even aware that the HPV vaccine can be given to their child. Previous research has shown that in the absence (or incipient stages) of an HPV vaccination program for boys, the unaware group accounts for 28-58% of a randomly selected sample of parents 13,14 and have significantly lower HPV knowledge compared to unengaged, undecided and decided not hesitant parents. 14 To better understand the longitudinal decision of vaccine hesitant parents we dichotomized vaccine hesitant parents-in parents of boys and girls-as two distinct entities: "flexible" Note: OR = adjusted odds ratio for decided to/vaccinated versus unengaged/undecided/decided not (reference category).…”
Section: Discussionmentioning
confidence: 99%
“…Then, we ran the multivariate model (final model) with predictors significantly associated with the outcome in bivariate analyses and predictor variables of interest i.e., policy change, ethnicity. 14 We used following logistic regression model diagnostic criteria 1 : Rank Discrimination Index C where C = 0.5 indicates random guessing and C = 1 perfect discrimination 2) Variation Inflation Factor (VIF) with a cut-off value of <10 to flag multicollinearity 23 and 3) Cessie-van Houwelingen goodness-offit test whereby p > 0.05 suggests no evidence to reject a good fit. 24 We calculated the Bayesian Information Criterion (BIC) 25 for the regression model including all variables and the final model and retained the model with the lowest BIC value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Research has illuminated parental attitudes and the utility of provider-oriented interventions, and multiple factors contributing to relatively stagnant coverage rates have been identified, including concerns about safety, efficacy and timing of vaccines. [5][6][7][8][9][10] Relatively little is known about the adolescent's perspective on vaccines, but it appears that some adolescents have an impact on the decision-making process and vaccine acceptance, highlighting the importance of understanding teen perspective. [11][12][13][14] The HPV vaccine is one of the most effective measures to protect adolescents against a variety of HPV-related cancers [15][16][17][18] , but uptake remains low.…”
Section: Introductionmentioning
confidence: 99%